Search of QSAR Models for Predicting the Antiprotozoal Activity and Cytotoxicity In Vitro of a Group of Pentamidine Analogous Compounds - Garcia-Domenech, Ramon; Denise Manhenje, Isabel; Monje, Yamileth; Lopez-Gonzalez, Adassa; Marco, Rafael; Tacho, Catalina; Galvez, Jorge (Letters in Drug Design & Discovery, 2011)
Molecular topology and multilinear regression analysis have been applied to achieve QSAR models for the prediction of the in vitro antiprotozoal activity against T. b. rhodesiense, P. falciparum as well as the cytotoxicity of a group of compounds analogs to pentamidine. Once the models were validated, a molecular screening was carried out for the search of new compounds showing high activity on both parasites and low cytotoxicity.
Keywords: trypanosomiasis